Entrepreneurship, Wage Employment and Control in an Occupational Choice Framework - Robin Douhan; Mirjam van Praag (Research Institute of Industrial Economics (IFN), 2009)
We combine two empirical observations in a general equilibrium occupational choice model. The first is that entrepreneurs have more control than employees over the employment of and accruals from assets, such as human capital. The second observation is that entrepreneurs enjoy higher returns to human capital than employees. We present an intuitive model showing that more control (observation 1) may be an explanation for higher returns (observation 2); its main outcome is that returns to ability are higher in higher control environments. This provides a theoretical underpinning for the control-based explanation for higher returns to human capital for entrepreneurs.
Keywords: I20; J24; J31; L26; 330; Entrepreneurship; Ability; Occupational Choice; Human Capital; Wage Structure; Berufswahl; Entrepreneurship-Ansatz; Selbstständige; Angestellte; Humankapital; Lohnstruktur; Bildungsertrag; Allgemeines Gleichgewicht; Theorie